Evaluating the Policy of Smart City in Indonesia - Amri, Whan Augustin Ainul; Amri, Lala Hucadinota Ainul; Puspitasari, Dyah Ayu Kunthi (IJOSMAS, 2025)
Smart city development is a crucial component of urban transformation in Indonesia. However, policies and approaches to this concept vary, depending on institutional and sectoral focus. This article examines the differences in smart city policy approaches between the digital communications perspective and the physical infrastructure (PUPR) perspective. Through a literature review of academic documents and national policies, this article identifies that the digital communications approach emphasizes strengthening information technology-based public service systems, bold citizen participation, and data transparency. Meanwhile, the PUPR approach focuses more on developing basic infrastructure such as transportation, drainage, housing, and city utilities integrated with technologies like the Internet of Things (IoT). The study shows that both approaches have their respective advantages and challenges, but are not yet fully coordinated in policy practice. This article emphasizes the importance of cross-sector synchronization for effective, efficient, and sustainable smart city development.